PENERAPAN TEKNIK DISKUSI KELOMPOK DALAM BIMBINGAN KELOMPOK TERHADAP MOTIVASI BELAJAR SISWA DI MASA PANDEMI COVID-19 - Naila Sa'adah; Asep Samsudin; Tuti Alawiyah (IKIP Siliwangi, 2022)
This research is motivated by the corona virus pandemic that affects the provision of guidance and counseling services in schools. Group guidance services are provided to students who have learning motivation problems. To support group guidance services, the right technique is needed, namely group discussion techniques. This research was conducted using qualitative research methods with data collection through interviews, observation, and documentation. The subjects in this study were class XI students with a sample of 5 students based on the recommendations of the BK teacher and homeroom teacher who tended to have learning motivation problems. The results of the study showed that there was a change in students after being given group guidance services with group discussion techniques compared to before the service was carried out. So that the application of group guidance services can increase student motivation in class XI MIPA 8 at SMAN 2 Cimahi. Keywords: Group Guidance Service, Group Discussion Technique, Motivation to Learn